Testing thousands of nanoparticles in vivo using DNA barcodes. (September 2018) - Lokugamage, Melissa P.; Sago, Cory D.; Dahlman, James E.
Abstract: Nanoparticles improve drug efficacy by delivering drugs to sites of disease. To effectively deliver a drug in vivo, a nanoparticle must overcome physical and physiological hurdles that are not present in cell culture, yet in vitro screens are used to predict nanoparticle delivery in vivo . An ideal nanoparticle discovery pipeline would enable scientists to study thousands of nanoparticles in vivo . Here, we discuss technologies that enable high throughput in vivo screens, focusing on DNA barcoded nanoparticles. Graphical abstract: